Navigating the diagnostic gray zone: a challenging case of pancreatic high-grade neuroendocrine neoplasm - Brooke Mullen; Albert L. Sy; Priscila Dias Goncalves; M. Lisa Zhang (BMC, 2024)
Abstract Background Grade 3 neuroendocrine tumor (G3 PanNET) and poorly differentiated neuroendocrine carcinoma (PanNEC) of the pancreas are considered distinct entities from a biological and prognostic perspective but may have overlapping features complicating a definitive diagnosis. Case Presentation A 52-year-old female presented with a pancreatic body mass and liver lesions. Initial biopsies showed variable lower- and higher-grade morphologies and modestly elevated Ki67 proliferation index up to 30%, leading to a diagnosis of G3 PanNET. The patient underwent everolimus treatment followed by surgical resection, revealing a complex tumor with features of both G3 PanNET and PanNEC, including admixed well- and poorly differentiated morphologies, modestly elevated hotspot Ki67 of 28%, retained ATRX/DAXX expression, and loss of RB expression. The final diagnosis rendered was "high-grade neuroendocrine neoplasm" with discussion of both entities in the differential. Post-operatively, the patient remains alive with stable metastases. Conclusions This case highlights the diagnostic complexities of distinguishing G3 PanNET and PanNEC even with the support of ancillary immunohistochemical and molecular studies. In addition, such cases raise the possibility that G3 PanNET and PanNEC may lie on a spectrum of disease with potential biological overlap.